2004
DOI: 10.1086/421472
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosisH37Rv:ΔRD1 Is More Virulent thanM. bovisBacille Calmette‐Guérin in Long‐Term Murine Infection

Abstract: Region of difference (RD1) genes are present in virulent Mycobacterium tuberculosis but not the vaccine strain M. bovis bacille Calmette-Guérin (BCG). The deletion of RD1 from M. tuberculosis produces an attenuation strikingly like that of BCG, which suggests the use of RD1 mutant strains for improvement of the tuberculosis (TB) vaccine. We performed long-term murine infection with M. tuberculosis H37Rv: Delta RD1 and BCG. Mice infected with H37Rv: Delta RD1 gained less weight than did BCG-infected control mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 15 publications
(34 reference statements)
5
30
0
2
Order By: Relevance
“…Importantly, BCG::RD1 displays increased virulence which, however, does not attain that of M. tuberculosis H37Rv. This result is in accordance with the very recent observation that M. tuberculosis H37Rv deleted for the whole RD1 region is more virulent than BCG in long-term mouse infection (21), pointing out the contribution of other M. tuberculosis-specific genes or genomic regions in virulence. This increased growth of BCG::RD1 seems to be intimately linked to in vivo conditions since no difference in growth rate was observed in vitro for BCG::RD1 compared with BCG in the conditions tested.…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, BCG::RD1 displays increased virulence which, however, does not attain that of M. tuberculosis H37Rv. This result is in accordance with the very recent observation that M. tuberculosis H37Rv deleted for the whole RD1 region is more virulent than BCG in long-term mouse infection (21), pointing out the contribution of other M. tuberculosis-specific genes or genomic regions in virulence. This increased growth of BCG::RD1 seems to be intimately linked to in vivo conditions since no difference in growth rate was observed in vitro for BCG::RD1 compared with BCG in the conditions tested.…”
Section: Discussionsupporting
confidence: 92%
“…This has led to the hypothesis that the ongoing evolution of BCG has resulted in the loss of regions involved in virulence and has caused the vaccine to become overattenuated (21). Despite the plethora of genomic data, the phenotypic consequence of mutations in BCG strains has not been convincingly demonstrated beyond the original loss of the RD1 region (18,24,34). Intriguingly, Raghavan and colleagues demonstrated that the transcription of genes within the RD2 region is influenced by the RD1-associated secreted virulence factor EspR, presenting a conceptual link between the deletion of these two elements from BCG (26).…”
Section: Discussionmentioning
confidence: 99%
“…42 This suggests that additional genetic lesions contribute to the attenuation of BCG. Whole genome sequence comparison reveals 2,223 single nucleotide polymorphisms (SNPs) between BCG-Pasteur 1173P2 and M. tb H37Rv, and 736 SNPs between BCG-Pasteur and M. bovis AF2122/97.…”
Section: Bcg: a Brief Historymentioning
confidence: 99%